2012
DOI: 10.1371/journal.pone.0036080
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Relationship and Adherence to Antipsychotic Medication in Schizophrenia

Abstract: ObjectivePrevious research has shown that a better therapeutic relationship (TR) predicts more positive attitudes towards antipsychotic medication, but did not address whether it is also linked with actual adherence. This study investigated whether the TR is associated with adherence to antipsychotics in patients with schizophrenia.Methods134 clinicians and 507 of their patients with schizophrenia or a related psychotic disorder participated in a European multi-centre study. A logistic regression model examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 30 publications
3
82
1
6
Order By: Relevance
“…As would be expected based on the treatment adherence literature [35][36][37][38], the experts endorsed positive expectations about the potential benefits of treatment, a good therapeutic alliance with the HCP, good occupational and cognitive functioning, and a readiness to change among characteristics that are very likely to promote engagement with DHTs. The survey responses suggested that many of the characteristics that promote favorable outcomes in any psychosocial intervention are similar to those that promote favorable outcomes when interventions are delivered via a DHT, except that patients will also need access to and the ability to use technology.…”
Section: Identifying Appropriate Patientsmentioning
confidence: 70%
“…As would be expected based on the treatment adherence literature [35][36][37][38], the experts endorsed positive expectations about the potential benefits of treatment, a good therapeutic alliance with the HCP, good occupational and cognitive functioning, and a readiness to change among characteristics that are very likely to promote engagement with DHTs. The survey responses suggested that many of the characteristics that promote favorable outcomes in any psychosocial intervention are similar to those that promote favorable outcomes when interventions are delivered via a DHT, except that patients will also need access to and the ability to use technology.…”
Section: Identifying Appropriate Patientsmentioning
confidence: 70%
“…Engaging people with the most serious disorders in a trusting relationship (McCabe et al 2012;Dixon et al 2016) is essential. Coercion can undermine success: a perceived loss of autonomy may create a more negative dynamic between client and clinician (Theodoridou et al 2012), while a good relationship improves quality of life and functional outcomes (Catty et al 2010(Catty et al , 2011.…”
Section: Engagement and Relationshipmentioning
confidence: 99%
“…Knowing more about the consumer as an individual and not just their diagnosis or presenting problem reduces the likelihood of a consumer feeling labelled or judged, as they feel they are being related to as a person [32]. Outcomes and compliance with management plans and treatment has been shown to improve if there is a good therapeutic relationship [33,34].…”
Section: Interpersonal/therapeutic Factorsmentioning
confidence: 99%